2015
DOI: 10.5194/amt-8-4681-2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mediterranean hail-bearing storms using an operational polarimetric X-band radar

Abstract: Abstract. This work documents the effective use of X-band radar observations for monitoring severe storms in an operational framework. Two severe hail-bearing Mediterranean storms that occurred in 2013 in southern Italy, flooding two important Sicilian cities, are described in terms of their polarimetric radar signatures and retrieved rainfall fields. The X-band dual-polarization radar operating inside the Catania airport (Sicily, Italy), managed by the Italian Department of Civil Protection, is considered her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…Past studies [22][23][24][25][26][27][28][29] have shown that locally deployed dual-polarization X-band radar systems can contribute higher resolution rain rate estimations and improved rainfall quantification accuracies than the lower frequency (C-band and S-band) long-range operational radar systems. These short-range radar systems could potentially be used to fill in coverage gaps of operational weather radar networks, which is particularly important for advancing early warning of precipitation driven hydrological hazards (flash floods, landslides, debris flows, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Past studies [22][23][24][25][26][27][28][29] have shown that locally deployed dual-polarization X-band radar systems can contribute higher resolution rain rate estimations and improved rainfall quantification accuracies than the lower frequency (C-band and S-band) long-range operational radar systems. These short-range radar systems could potentially be used to fill in coverage gaps of operational weather radar networks, which is particularly important for advancing early warning of precipitation driven hydrological hazards (flash floods, landslides, debris flows, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly based on [17] and is tailored to identify meteorological targets, with a particular emphasis on the hydrometeors involved in convective events. Recent updates are described in [9,27], for X-band and C-band, respectively, that show the membership functions used. Such functions are not so different from those reported in the literature and therefore the results obtained should not be significantly influenced by the choice of FL classifier.…”
Section: Support Vector Machine Implementation Of Hcamentioning
confidence: 99%
“…The case studies considered occurred on 21 February and 21 August 2013 in Sicily and were observed by the Selex-Gematronik 50 DX system (with a 3 dB antenna beamwidth of 1.3 • and a transmit peak power of 50 kW) of the Department of Civil Protection of Italy, operational at the airport of Catania [27]. The radar performed a volume scan made of 12 sweeps at different antenna elevation angles ranging from 1 • to 21.6 • , and an additional one at vertical incidence.…”
Section: X-band Datasetmentioning
confidence: 99%
“…The conversion coefficients a q , b q , and c q are defined so that the resulting rain rate R q is in (mm·h −1 ), where the subscript q indicates one of the three estimation formulas through the labels "Z", "K", and "DR". Finally, Equation (4) (with label q = KZ), adapted from the formulation proposed in [28], is a weighted combination of R K and R Z estimates from Equations (2) to (3) proposed by [29,30], respectively. In this case, the value of the weight (w) is set up so that the rain estimation that comes out using K dp , i.e., R K , weighs more for higher precipitation rates than that when making use of Z hh and Z dr only, i.e., R DR .…”
Section: Qpe From Radar Observablesmentioning
confidence: 99%